Macrophage polarization and its impact on idiopathic pulmonary fibrosis - Ge, Zhouling; Chen, Yong; Ma, Leikai; Hu, Fangjun; Xie, Lubin (Frontiers in Immunology, 2024)
Idiopathic pulmonary fibrosis (IPF) is a lung disease that worsens over time, causing fibrosis in the lungs and ultimately resulting in respiratory failure and a high risk of death. Macrophages play a crucial role in the immune system, showing flexibility by transforming into either pro-inflammatory (M1) or anti-inflammatory (M2) macrophages when exposed to different stimuli, ultimately impacting the development of IPF. Recent research has indicated that the polarization of macrophages is crucial in the onset and progression of IPF. M1 macrophages secrete inflammatory cytokines and agents causing early lung damage and fibrosis, while M2 macrophages support tissue healing and fibrosis by releasing anti-inflammatory cytokines. Developing novel treatments for IPF relies on a thorough comprehension of the processes involved in macrophage polarization in IPF. The review outlines the regulation of macrophage polarization and its impact on the development of IPF, with the goal of investigating the possible therapeutic benefits of macrophage polarization in the advancement of IPF.